Injection Opioid and Injection Methamphetamine Use in the Rural United States: A Systematic Review and Network Analysis. (April 2020) - Novack, Luke Michael; Carrasco, Kimberly Gocchi; Tyler, Kimberly A.; Dombrowski, Kirk; Habecker, Patrick
The abuse of opioid and methamphetamine is a public health crisis in the United States, particularly in rural areas where injection drug use is common. This systematic review of rural injection drug use synthesized the research on injection of opioids and methamphetamine use and assessed the similarity of their research findings to the field of rural injection drug use in the United States. A citation network analysis was used to support the assessment of research similarity and provided a visualization of the field. This citation network analysis exposed a gap in the literature revealing that the state of research may not be fully applicable to the field in its entirety in the United States. In summary, this review provides a representative overview of the state of research in the field of injection drug use. Future research should conduct studies on rural drug use in areas of the country not represented in this review.